Implementation of Village Pharmacies (Apotek Desa/Klinik Desa) in Indonesia: Challenges, Opportunities, and Impact on Primary Care Access – A Scoping Review - Wahyuni, Sri; Manik, Umi Chairani; Rahmadani, Rahmadani (Indonesian Journal of Science and Pharmacy, 2025)
The Indonesian government launched the Village Pharmacy (Apotek Desa/Klinik Desa) program in 2025, integrated with Merah Putih Village Cooperatives, to improve access to essential medicines and primary healthcare services in rural areas. This scoping review aimed to map the implementation of Apotek Desa/Klinik Desa, identify challenges and opportunities, and evaluate its impact on primary care access. Guided by Arksey and O’Malley’s framework guidelines, a systematic search was conducted in PubMed, Scopus, Google Scholar, Garuda, Sinta, and official Ministry of Health websites. Literature published between 2015 and March 2026 in English or Indonesian was included. Data were extracted and synthesized thematically. Seven studies and policy documents were included. The program is in its early implementation stage with infrastructure preparation in over 100 mock-up sites. Key challenges include pharmacist shortages in remote areas, regulatory gaps, limited infrastructure, and poor inter-sectoral coordination. Opportunities involve better availability of essential medicines, reduced travel and out-of-pocket costs, local job creation, and improved equity in primary care. However, empirical evidence on clinical and economic impacts remains limited. Apotek Desa/Klinik Desa shows strong potential to reduce health disparities and support Universal Health Coverage in Indonesia. Successful rollout requires strengthened regulation, pharmacist capacity building, quality supervision, and rigorous impact evaluation.